Foreign Investment in Agricultural Production : Opportunities and Challenges - Songwe, Vera; Deininger, Klaus (World Bank, Washington, DC, 2012)
The recent surge in food and fuel prices has prompted countries with high dependence on food imports to try and lock in future food supplies through direct investment in agricultural production in other countries. The price surges also led to a wave of proposals to invest in biofuels investments in agricultural land. While such investment can provide large benefits, it also carries considerable risks both to investors and citizens in the locality of the investment. To ensure that investments provide broad benefits and effectively contribute to larger development outcomes, enforceable property rights and contractual agreements in many developing countries need to be strengthened. This note considers how development partners can help countries create the pre-conditions for investment and proposes a governance framework to establish minimum standards for it.